An Analysis of the Impact of Customer Service Quality on Customer Satisfaction at Sephora, Summarecon Mall Bandung - Hendriana, Tengku Ine; Dwiyanti, Ully; Maharani, Luthfika Dewi; Maipalna, Pepen; Faturrohman, Faturrohman; Susilawati Sugiana, Neng Susi (Jurnal Komputer Bisnis, 2025)
This study aims to explore the dimensions of service quality and their impact on customer satisfaction within a retail service context. As consumer expectations continue to rise alongside the growth of the business sector in Indonesia, understanding customer perceptions has become increasingly critical for sustaining competitive advantage. The research adopts a qualitative approach to gain in-depth insights, involving semi-structured interviews with 20 respondents who have experienced direct service interactions in a prominent retail company. Data were analyzed using thematic content analysis to identify recurring themes related to service quality, responsiveness, and customer loyalty. The findings reveal that five key factors reliability, responsiveness, empathy, assurance, and tangibles play a significant role in shaping customer satisfaction. Among these, responsiveness and empathy emerged as the most influential in creating a positive service experience. Additionally, the study highlights how personalized communication and consistent service delivery contribute to long-term customer retention. From a practical standpoint, the results suggest that retail businesses should invest in employee training programs that enhance interpersonal skills and customer empathy. The unique contribution of this study lies in its qualitative focus within a largely quantitative research domain, offering rich, narrative- based insights that deepen understanding of service quality dynamics. This research contributes to the broader field of service management by offering actionable strategies for improving customer satisfaction through tailored service improvements.